Network Disaster Recovery Design Using Hot Standby Router Protocol (HSRP) - Harahap, Abdul Rachman; Tommy, Tommy; Handoko, Divi (Al'adzkiya International of Computer Science and Information Technology (AIoCSIT) Journal, 2021)
Computer network infrastructure located in a certain area is inseparable from possible disasters such as natural disasters caused by geological and demographic factors, fire - be it environmental factors or human error, or attacks on systems such as viruses or worms. Therefore, in building a network infrastructure we also need a network backup plan and recovery in the event of a disaster on the network infrastructure that supports the delivery of information. The backup network infrastructure must be in a different location with the main network infrastructure to anticipate major disasters. This research will implement the Hot Standby Router Protocol (HSRP), which is designed to support irregular IP traffic failures under certain circumstances. The purpose of this research is to implement Disaster Recovery Plans on technology related to network recovery, Provide recommendations for Disaster Recovery Institutions. The softaware used is GNS3. Keyword: Network, Backup, HSRP